Variable sex-specific mortality due to shorebird predation on a fiddler crab - Ribeiro, Pablo Damián; Iribarne, Oscar Osvaldo; Jaureguy, Luciano; Navarro, Diego; Bogazzi, Eugenia (Canadian Journal of Zoology)
Male fiddler crabs compete for access to mates mainly by displaying an enlarged claw. One cost of this large claw is presumed to be higher exposure to predators. The fiddler crab Uca uruguayensis is used as a food source by several Neotropical migratory shorebirds. We investigated whether crab density and male claw-waving behaviour increase predation by shorebirds. The sex ratio of crabs on the surface was strongly male biased. Male crabs showed a daily succession of feeding–waving–feeding activities and their dry mass at the site decreased with a high density of crabs, suggesting stronger male–male competition than at sites with a low density of crabs. Sex-specific predation varied according to shorebird species. The Ruddy Turnstone (Arenaria interpres) preyed intensively on male crabs when they were courting and at sites with a high density of crabs, the Black-bellied Plover (Pluvialis squatarola) and the Lesser Golden Plover (Pluvialis dominica) preyed on crabs of both sexes, and the Whimbrel (Numenius phaeopus) foraged intensively on females. When estimating the net effect of all predators, we found that the four shorebird species together were able to consume between 0.1 and 0.2% of the crab population, and consumption did not differ between the sexes of crabs. These mortality rates indicate a low source of mortality, likely unable to produce deviations in the sex ratio of the population. Thus, our results indicate that a trait thought to be sexually selected does not necessarily lead to a disproportionate increase in mortality due to predation. Les crabes violonistes mâles font compétition pour les femelles principalement en exhibant leur pince élargie. Un des coûts associés à cette grande pince est sans doute une exposition accrue aux prédateurs. Le crabe violoniste Uca uruguayensis sert de nourriture à de nombreux oiseaux de rivage migrateurs néotropicaux. Nous avons vérifié si la densité des crabes et le comportement d'agitation de la pince par les mâles augmentent la prédation par les oiseaux de ...